Hak Cipta Dalam Media Sosial: Mengatasi Pembajakan Digital Dalam Regulasi Hukum (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Copyright is an exclusive right granted to creators to protect their intellectual works. The importance of copyright protection has increased with advances in digital technology and the widespread use of social media as a means of content distribution. Digital platforms such as YouTube, Instagram, TikTok, and various other streaming services facilitate the distribution of digital works, but also give rise to problems such as piracy and the use of works without the permission of the copyright owner. This digital piracy can result in economic and moral losses for creators. This study aims to analyze the application of copyright in the context of social media and examine the legal regulations governing copyright protection to address digital piracy in Indonesia. The method used in this study is a normative legal research method with a statutory and conceptual approach. The results show that legal protection for digital works is regulated by Law Number 28 of 2014 concerning Copyright and is strengthened by Law Number 1 of 2024 concerning Electronic Information and Transactions. These two regulations provide a legal basis for protecting the moral and economic rights of creators and authorize the government to block access to content that infringes copyright. These regulations are expected to reduce digital piracy and create a digital ecosystem that respects intellectual property rights.